Odpowiedzi

Najlepsza Odpowiedź!
2009-11-30T19:04:26+01:00
A) (x-5)(x+5)+2xy= x²-5x+5x+25+2xy= x²+2xy+25
b) (3-a)(6-3a)+3a= 18-6a-9a+3a²+3a=-12a+18+3a²
c) (-2+x)(2+x)=-4+x²-2x+2x=x²-4
d) (-4-x)(4+2x)= -16-4x-2x²-8x= -16-2x²-12x
e) (-2-2x)(-4+3x)=8+8x-6x²-6x=8+2x-6x²
f) (-6-3x)(-5-8x)= 30+15x+24x²+48x=30+24x²+63x
2009-11-30T19:25:43+01:00
(x-5)(x+5)+2xy=x²+5x-5x-25+2xy=x²-25+2xy
b) (3-a)(6-3a)+3a=18-9a²-6a+3a²+3a=-6a²-3a+18
c) (-2+x)(2+x)=-4-2x+2x+x²=x²-4
d) (-4-x)(4+2x)=-16-8x-4x-2x²
e) (-2-2x)(-4+3x)=8-6x+8x-6x²=6x²+2x+8
f) (-6-3x)(-5-8x)= 30+48x+15x+24x²=24x²+63x+30